(untitled) (Global Journal of Human-Social Science, 2021)
Literature is one of the finest ways to express the human art and creativeness, therefore, is a path to reach the understanding of human nature. In this article, we will discuss the use of literature in group debate of elders which participated in a senior program of a Brazilian university as a resource to stimulate a personal discovery of inner resources to deal with this challenging period of life during the Covid 19 pandemic in 2020. Our participation started in 2017 with a group formed by men and women above 60 years old attending this program. Until 2019, there were 65 participants in a yearly program, but in 2020 there was a variation between 40-70. The experience to be discussed derives from an aesthetic attitude, starting with literary reading followed by a group discussion in order to stimulate affective social bonds among the participants. Further discussed themes were the impact of the online version and the use of technology in a senior group.